MicroCT-Based Virtual Histology Evaluation of Preclinical Medulloblastoma - Prajapati, Suresh I.; Kilcoyne, Aoife; Samano, Aislynn K.; Green, Dustin P.; McCarthy, Steven D.; Blackman, Barron A.; Brady, Michelle M.; Zarzabal, Lee Ann; Tatiparthy, Arun K.; Sledz, Timothy J.; Duong, Timothy; Ohshima-Hosoyama, Sachiko; et al. (Molecular imaging and biology, 2011)
Purpose The purpose of this paper is to validate a rapid and cost-effective ex vivo technique, microCT-based virtual histology, as an alternative to MRI imaging for assessing the therapeutic response in genetically engineered mouse models of cancer. Procedures All animal procedures were conducted in accordance with the Guidelines for the Care and Use of Laboratory Animals and were approved by the Institutional Animal Care and Use Committee (IACUC) at the University of Texas Health Science Center at San Antonio. MRI imaging was performed on 6-week-old, bortezomib-treated genetically engineered Patched1, p53 mice that recapitulate the characteristics of human medulloblastoma. After MRI scans, the same mice were euthanized to collect brain or spine samples for virtual histology staining followed by microCT scanning. Results Nine-micrometer resolution ex vivo micro X-ray computed tomography (microCT)-based virtual histology images were qualitatively reflective of high-field live animal images obtained with magnetic resonance imaging (MRI) and histopathology. Cerebellar volumes on microCT-based virtual histology correlated closely with MRI cerebellar volumes ( R = 0.998). MRI and microCT-based virtual histology both indicated a significant difference between cerebellar volumes of untreated and treated mice ( p = 0.02 and p = 0.04, respectively). The ex vivo microCT method also allowed a 7,430-fold improvement in voxel resolution (voxel volume of 729 μm 3 for 9-μm isometric resolution microCT vs. 5,416,800 μm 3 for 400 × 111 × 122 μm resolution MRI) at a 28% cost savings ($400 vs. $555 per animal). Conclusion The ex vivo , en bloc technique of microCT-based virtual histology matched MRI in reflecting histopathology. MicroCT-based virtual histology proved to be a more cost-effective technique and less labor-intensive. On the other hand, MRI provides ability to perform in vivo imaging, faster scanning and lower radiation dose by sacrificing the spatial resolution. Thus, both in vivo MRI and ex vivo microCT-based virtual histology are effective means of quantitatively evaluating therapeutic response in preclinical models of cerebellar tumors including the childhood cancer, medulloblastoma.